Control of wiregrass (Sporobolus indicus) by planting Panicum maximum varieties - Sardi?as, Yurangel; Varela, M.; Padfilla, C?sar; Torres, Verena; Noda, Aida; Fraga, Nidia (Cuban Journal of Agricultural Science, 2011)
The control of wiregrass (Sporolobus indicus) was assessed by the renewal of an improved pasture in state of degradation, with 50 % of wiregrass and 20 of Guinea grass, using varieties of the Panicum genus. The treatments were: Guinea grass Likoni, Common, Mombaza, Tanzania and tillage without sowing. The performance of the treatments was characterized through univariate and multivariate analyses. It was proved that Guinea grass Likoni and Mombaza had better control of wiregrass. As the prevalence of the Guinea grass for both varieties Likoni and Mombaza was increased, the population density was lower in wiregrass. The biomass availability was similar in both, in respect to the prevalence of this weed. The percentage of Guinea grass was superior to 60 %, even in the tillage without sowing, in respect to the initial vegetation sampling. However, the highest percentage of the improved pasture was found in Likoni and Mombaza. The Tanzania and the Common varieties exerted lower control in wiregrass, or quite similar as to that of the tillage without sowing. It is concluded that the Likoni and Mombaza cultivars controlled wiregrass much more. The multivariate analysis allowed establishing the relationship between the variables, and explaining integrally the results of the renewal. The use of the Likoni and Mombaza varieties as alternative for controlling wiregrass in improved pastures in state of degradation is recommended. Key words: grass, wiregrass, varieties, Panicum, Biplot.